2007
DOI: 10.1203/01.pdr.0000251612.16069.4b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Neonatal Ischemic Injury Models Using Magnetic Resonance Imaging

Abstract: Using an 11.7-Tesla magnetic resonance imaging (MRI) scanner in 10-d-old rat pups we report on the evolution of injury over 28 d in a model of neonatal stroke (transient filament middle cerebral artery occlusion, tfMCAO) and a model of hypoxicischemic injury (Rice-Vannucci model, RVM). In both models, diffusion-weighted imaging (DWI) was more sensitive in the early detection of ischemia than T2-weighted imaging (T2WI). Injury volumes in both models were greater on d 1 for DWI and d 3 for T2WI, decreased over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 21 publications
4
68
2
1
Order By: Relevance
“…As visualized by MRI, cytotoxic edema usually precedes the development of vasogenic edema (6,17,18). Deletion of AQP4 appears protective against the development of cytotoxic edema and results in smaller infarct volumes (10).…”
Section: Discussionmentioning
confidence: 99%
“…As visualized by MRI, cytotoxic edema usually precedes the development of vasogenic edema (6,17,18). Deletion of AQP4 appears protective against the development of cytotoxic edema and results in smaller infarct volumes (10).…”
Section: Discussionmentioning
confidence: 99%
“…13,74,78,79 Figure 1B shows that diffusion-weighted MRI depicts expansion of tissue 'at risk' associated with longer MCAO duration. Other MRI modalities have been proven useful in determining the extent of microcirculatory disturbances during MCAO and after reperfusion (perfusion-sensitive MRI), 76 disruption of the blood-brain barrier (BBB) (Gd-enhanced T1W imaging), 76 elucidation of the evolving injury (T2W imaging), 56,73,80 and changes in brain connectivity after injury during the neonatal period (diffusion tensor imaging). 81 Studies in tMCAO and H-I models in neonatal rodents have shown that although the components of injury that induce cell death and brain injury are similar to those occurring in experimental models of preterm injury-excitotoxic, oxidant, and inflammatory components-the targeted cell populations and regions affected by cerebral hypoxia and ischemia are different.…”
Section: Animal Models and The Underlying Mechanisms Of Perinatal Artmentioning
confidence: 99%
“…The variable time course of T2 and ADC responses reveals the underlying tissue pathologic processes. In the setting of cerebral ischemia, previous investigations have shown that the decrease in ADC often returns to normal values (pesduonormalization) while T2 values increase at the 7-day postinjury timepoint (14). In light of our present findings, the neuroimaging interpretations may not be uniform and should be addressed within the context of the triggering pathology.…”
Section: Discussionmentioning
confidence: 50%
“…ADC values are influenced by a host of intracellular and extracellular constituents that vary with the nature of cellular barriers (32). A variety of brain pathologies can be identified using DWI, including stroke (14) and seizures (13), in which the initial decrease in ADC occurs simultaneously with glial cell proliferation, neurodegeneration, or cytotoxic edema (13,14). At 1 week after 56 Fe exposure, there was a significant drop in brain ADC values in the absence of evident histopathology except for the subtle astrocytic hypertrophy at 4 Gy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation